The uncharted flight of Olivia West - Ackerman, Sara (Mira, 2024)
In 1987, when she inherits a piece of land, Emma finds a small plane in disrepair and her great uncle's journal that tells the story of Livy Jones, the woman who piloted his plane when he fell ill, and, with new purpose, works to secure Livy's place in the aviation hall of fame.